P150 Exploiting I-wave rhythmicity to optimize the stimulus-response relationship for TMS of M1 - van Bellen, J.; Takemi, M.; Karabanov, A.N.; Siebner, H.R. (Clinical neurophysiology, 2017)
Repetitive Transcranial Magnetic Stimulation (TMS) of the primary motor cortex (M1) can modulate corticospinal excitability beyond the time of stimulation, but the after-effects are subject to substantial variability. One determining factor are inter-individual differences in the way TMS stimulates the intracortical circuits that generate the descending volleys (I-waves) in the corticospinal tract. We systematically studied possibilities to utilize individual I-wave rhythmicity to enhance the efficacy of low-intensity TMS of M1 to excite corticospinal output. In healthy individuals, we recorded the motor evoked potential (MEP) evoked by paired, triple and quadruple pulse TMS. The inter-pulse interval (IPI) was adjusted to the individual I1-peak latency or the trough between the I1- and I2-wave. TMS used biphasic pulses with the second phase inducing a posterior-to-anterior current in M1. Paired, triple and quadruple pulse TMS at individual I-wave peak latency evoked larger MEP amplitudes than single-pulse TMS or paired, triple and quadruple pulse TMS at the I1-I2 trough. I1-peak latency facilitation was already visible at 70% resting motor threshold and was comparable for paired, triple and quadruple pulse TMS. A control experiment showed significant I1-peak latency facilitation also relative to a control condition in which IPI was shorter than individual I1-latency. Our preliminary study results support our hypothesis that I-wave interaction can be utilized to optimize the efficacy of TMS over M1 to excite the corticospinal output neurons. The effects are already maximal when using paired-pulse TMS, as triple pulse or quadruple-pulse TMS did not result in additional MEP facilitation. The use of individually adjusted paired-pulse TMS at I-wave latency might help to reduce inter-individual variability of repetitive TMS over human M1. This work was supported by the Lundbeck Foundation (Grant of Excellence “ContAct” R59 A5399) and the Novo Nordisk Foundation (Interdisciplinary Synergy Programme Grant ”BASICS” NNF14OC0011413).